2023
DOI: 10.1002/suco.202300421
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of ductility of concrete columns under horizontal seismic load

Wei Chang,
Meijing Hao,
Wenzhong Zheng

Abstract: The ductility of concrete columns, which determined the deformability of concrete columns, was an important parameter in evaluating the safety of framework structures under horizontal seismic loads. In this paper, 231‐group test data for evaluating the ductility of concrete columns under seismic loads were collected to establish a reliable database. The effects of investigated parameters including the compressive strength of concrete, the lateral confinement of stirrups, the ratio and yield strength of longitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…These variables were widely addressed in previous studies. Bae 10 showed a strong influence on the plastic hinge length of reinforced concrete column while Chang et al 26 reported a strong influence on the ductility of RC columns.…”
Section: Parametric Study On Plastic Hinge Length and Lateral Load-di...mentioning
confidence: 98%
“…These variables were widely addressed in previous studies. Bae 10 showed a strong influence on the plastic hinge length of reinforced concrete column while Chang et al 26 reported a strong influence on the ductility of RC columns.…”
Section: Parametric Study On Plastic Hinge Length and Lateral Load-di...mentioning
confidence: 98%